The anthropological analysis of the nasal morphology of Dayak Kenyah population in Indonesia as a basic data for forensic identification - Maria Istiqomah Marini; Hastomo Angrosidy; Arofi Kurniawan; Mieke Sylvia Margaretha (Elsevier, 2020)
The primary intention of forensic identification is the establishing of human identity, including sex, race, and ages. The nasal index is one of the important parameters to determine race and sex through the nasal morphology. Therefore, basic data of nasal index is necessary to be specifically used in observing nasal morphology variation that has been influenced by regional and climatic factors. This study conducted in the Sub-Dayak Kenyah population in North Kalimantan, Indonesia, as an indigenous population of Kalimantan Island. The nasal index mean and SD of males and females were 77,87 ± 10,8 and 78,46 ± 7,97 respectively. The dominant type of nasal shape for Dayak Kenyah males and females was mesorrhine with the second most common type was platyrrhine. There was a difference in the nasal shape between the present study and the previous study. The results of this study can be used to trace the origin of populations in Indonesia, especially North Kalimantan and important for the database in forensic science and anthropology. Keywords: Nasal index, Nasal morphology, Dayak Kenyah population of North Kalimantan